PEMBUATAN BAHAN AJAR FISIKA BERORIENTASI MODEL PEMBELAJARAN KEMAMPUAN BERPIKIR KRITIS PADA MATERI PENGUKURAN DAN VEKTOR KELAS X SMA SEMESTER I - Zainul Adha; Gusnedi Gusnedi; Letmi Dwiridal (Universitas Negeri Padang, 2018)
Characteristics of learning in high school physics material contain the needs of learners to think critically. The reality in the field showed Padang 8 senior high school exercise of learning physics is already using the materials, but not yet apply critical thinking ability of studensts. One of the solutions can be taken by develope learning materials which there learning model with increase critical thinking ability. This research has purrpose to produce learning materials improved critical thinking ability in material measurement and a decent vector with validity and practicalities. This includes research was conducted type of Research and development (R&D). Type of this research was a research and development by Sugiyono’s model. Data analysis techniques used, namely the analysis of the validity of the product and the analysis of the responses of teachers and students towards products. The resulting research products are on a very valid criteria with an average value of 88.58% and the response of teachers and students towards products that generated very good.